High fructose and streptozotocin induced diabetic impairments are mitigated by Indirubin-3-hydrazone via downregulation of PKR pathway in Wistar rats - Mary Priyanka Udumula (Nature Portfolio, 2021)
Abstract Metabolic disorders are becoming more common in young population due to increased consumption of carbohydrate rich diet, lack of physical activity and stress. Fructose is used as a sweetener in many carbonated beverages and is a known inducer of oxidative stress and hypertension. Up-regulation of the double-stranded RNA-dependent protein kinase (PKR) causes impairment in insulin signaling pathway and metabolic dysfunctions in type 2 diabetes mellitus. In the present study we investigated the role of PKR and associated pathways in high fructose (HF) and streptozotocin (STZ) induced diabetes and whether indirubin-3-hydrazone (IHZ), a novel PKR inhibitor can reverse the HF and STZ induced diabetic impairments in Wistar rats. Diabetes was induced by feeding rats 20% high fructose in drinking water for 6 weeks and by giving a single dose of STZ (35 mg/kg., i.p) at the end of week 5. Glucose and lipid levels were measured by using assay kits. Expression of PKR and its downstream genes were determined by immunohistochemistry, qRT-PCR and western blotting techniques. Histo-pathological studies were performed using H&E staining. Fibrosis was detected in insulin sensitive tissues and organs using Sirius red and Masson’s trichrome staining and apoptosis by TUNEL assay. HF and STZ induced hyperglycemia, fibrosis, oxidative stress, and inflammation in liver, pancreas, skeletal muscle and adipose tissue are mediated via PKR pathway and its downstream effectors, and these effects were attenuated by PKR inhibitor IHZ. Thus, inhibition of PKR can protect insulin sensitive organs and tissues from HF induced diabetic impairments via the inhibition of c-Jun N-terminal kinase (JNK) pathway.